Firm behaviour under alternative bidding systems for US OCS hydrocarbon leases - Federico Foders (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
One of the least settled issues in US offshore oil policy is the "best" scheme to capture resource rents arising from hydrocarbon production. This paper analyses the impact of alternative bidding systems on the intertemporal production path and on the firm's investment decision. It concludes that with the exception of the pure profit share system all other pure or mixed bidding systems are likely to have a distortive effect on production and, thus, eventually lead to a dissipation of economic rent. Further, no leasing system authorised by current public law is found to be neutral regarding investment decisions.
Keywords: 330